Deficiency of Adenosine Deaminase 2 in Adult Siblings: Many Years of a Misdiagnosed Disease With Severe Consequences - Springer, Jason Michael; Gierer, Selina A.; Jiang, Hong; Kleiner, David; Deuitch, Natalie; Ombrello, Amanda K.; Grayson, Peter C.; Aksentijevich, Ivona (Frontiers in Immunology, 2018)
Objective: Describe the clinical characteristics and histopathology findings in a family with two siblings affected with deficiency of adenosine deaminase 2 (DADA2). Both patients presented in childhood with polyarthritis and developed significant neurological and gastrointestinal features of DADA2 in early-adulthood, including variable degrees of immunologic and hematologic manifestations. Methods: CECR1 exon sequencing and serum adenosine deaminase 2 (ADA2) levels were performed to confirm the diagnosis of DADA2. Comparison of serum ADA2 levels were made to DADA2 patients, carriers and healthy controls in patient 2. Autopsy specimens from brain and liver tissues were submitted for analysis. Results: Both patients were found to carry a previously reported rare intronic missense mutation predicted to affect the transcript splicing (c.973-2A>G; rs139750129) and an unreported missense mutation p.Val458Asp (c.1373T>A; V458D). Both brothers started therapy with a tumor necrosis factor (TNF) inhibitor following the molecular diagnosis of DADA2 with good response and were eventually tapered off prednisone. However, Patient 1 died 18 months later due to complications of end-stage liver disease. His autopsy showed evidence for nodular hyperplasia of the liver often seen in common variable immune deficiency (CVID) and numerous small, old infarcts throughout the brain that had not been demonstrated on prior MRI/MRA imaging. Conclusion: These cases emphasize the importance of recognition of DADA2 in adults, compares CNS imaging modalities to pathologic findings and suggests similarities in liver pathology between DADA2 and CVID. MRI may not be most sensitive method to identify small subcortical infarcts in patients suspected to have DADA2.